The Role of Flare‐Driven Ionospheric Electron Density Changes on the Doppler Flash Observed by SuperDARN HF Radars. Issue 8 (24th August 2021) - Chakraborty, S.; Qian, L.; Ruohoniemi, J. M.; Baker, J. B. H.; Mclnerney, J. M.; Nishitani, N.
Abstract: Trans‐ionospheric high frequency (HF: 3–30 MHz) signals experience strong attenuation following a solar flare‐driven sudden ionospheric disturbance (SID). Solar flare‐driven HF absorption, referred to as short‐wave fadeout, is a well‐known impact of SIDs, but the initial Doppler frequency shift phenomena, also known as "Doppler flash" in the traveling radio wave is not well understood. This study seeks to advance our understanding of the initial impacts of solar flare‐driven SID using a physics‐based whole atmosphere model for a specific solar flare event. First, we demonstrate that the Doppler flash phenomenon observed by Super Dual Auroral Radar Network (SuperDARN) radars can be successfully reproduced using first‐principles based modeling. The output from the simulation is validated against SuperDARN line‐of‐sight Doppler velocity measurements. We then examine which region of the ionosphere, D, E, or F, makes the largest contribution to the Doppler flash. We also consider the relative contribution of change in refractive index through the ionospheric layers versus lowered reflection height. We find: (a) the model is able to reproduce radar observations with an root‐median‐squared‐error and a mean percentage error ( δ ) of 3.72 m/s and 0.67%, respectively; (b) the F‐region is the most significant contributor to the total Doppler flash (∼48%), 30% of which is contributed by the change in F‐region's refractive index, while the other ∼18% is due to change in ray reflection height. Our analysis shows lowering of the F‐region's ray reflection point is a secondary driver compared to the change in refractive index. Plain Language Summary: Sudden eruption of electromagnetic radiation from the Sun, also known as a solar flares, alters the physical properties of the ionosphere, creating ionospheric perturbations, commonly referred to as a sudden ionospheric disturbance (SID). The ionosphere perturbation following a solar flare disrupts the over the horizon radio communication channels on the dayside of the Earth, also known as shortwave fadeout. The ionospheric radio wave absorption effect during a solar flare‐driven SID is a well known and understood phenomena. However, the initial Doppler frequency shift, also known as "Doppler flash, " in the traveling radio wave is a newly discovered phenomena and not yet fully understood. This paper seeks to advance our understanding of the initial impacts of solar flares on the ionospheric properties. Key Points: Doppler flash is predominantly driven by changes in ionospheric refractive index The F‐region ionosphere contributes significantly to the Doppler flash Lowering of the F‐region reflection height is due to the flare‐driven weakening of upward ion‐drift